Association between nocturnal blood pressure variation and wake-up ischemic stroke. (October 2017) - Kwon, Hyuk Sung; Kim, Ji Young; Choi, Hojin; Lee, Seok Joon; Koh, Seong-Ho; Lee, Young Joo; Kim, Hyun Young; Kim, Hee-Tae; Kim, Juhan; Kim, Young Seo
Highlights: Patients with WUS had more severe stroke symptoms than patients with non-WUS. Variation in nocturnal blood pressure did not associated with occurrence of WUS. Clinical characteristics were not different between patients with WUS and non-WUS. Abstract: Ischemic stroke during nocturnal sleep, known as wake-up stroke (WUS), has been reported to have more severe symptoms and worse outcomes than non-WUS. However, studies on risk factors for WUS are scarce and the association between nocturnal blood pressure (BP) and WUS is unclear. In this study, we used ambulatory blood pressure monitoring (ABPM) to examine the association between WUS and variation in nocturnal BP. A total of 369 patients with ischemic stroke within one week were consecutively enrolled. ABPM was applied 1–2 weeks after the ictus because of possible reactive increments of BP; antihypertensive medications were delayed until ABPM. Patients were classified into two groups: WUS and non-WUS. Clinical characteristics, including ABPM parameters, were compared. Sixty-seven (18%) patients had WUS. In univariate analysis, patients with WUS had more severe stroke symptoms than patients with non-WUS. There were no differences in clinical characteristics. In addition, ABPM parameters, including nocturnal BP dipping and morning BP surge, were not associated with occurrence of WUS. Patients with WUS had more severe stroke symptoms and worse outcomes than those with non-WUS. Variation in nocturnal BP may not associated with the occurrence of WUS.